Expanding the role of the future zoo: Wellbeing should become the fifth aim for modern zoos - Rose, Paul E.; Riley, Lisa M. (Frontiers in Psychology, 2022)
Zoos and aquariums have an enormous global reach and hence an ability to craft meaningful conservation action for threatened species, implement educational strategies to encourage human engagement, development and behaviour change, and conduct scientific research to enhance the husbandry, roles and impacts of the living collection. The recreational role of the zoo is also vast- people enjoy visiting the zoo and this is often a shared experience amongst family and friends. Evaluating how the zoo influences this “captive audience” and extending its reach to include a compassionate approach to animals and people can further enhance the mission, value, and relevance of their work. The modern zoo’s current aims- Conservation, Education, Research and Recreation- provide useful foundations for the activities that zoos conduct at a local and national level. However, to improve sustainability of their actions and outcomes, we feel that Wellbeing should become the fifth aim of the modern zoo for the future- both from an animal perspective (ensuring that populations are managed according to prevailing behavioural needs) and from a human perspective (enhancing access to nature, promoting planetary friendly behaviour changes and ways of living, and advancing the wellbeing of the zoo’s workforce). This paper provides discussion and review of how Wellbeing is already a substantial part of what zoos work on as well as posing the idea of altering the Recreation aim of the zoo to one of Engagement, which potentially is more measurable and therefore can allow zoo researchers and managers further options for the collection of evidence on the local and global reach of their zoo’s aims. Education, Engagement, Conservation, Research and Wellbeing provide a more complete picture of the roles of the modern zoo for the animals (both in and ex situ), human visitors and workforce, and to society more widely